2007
DOI: 10.2298/abs0704303s
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B gene polymorphisms in patients from Serbia with ischemic cerebrovascular disease

Abstract: The plasma concentration of apoB has recently been reported to be the best lipid predictor of coronary heart disease. The possible associations of genetic markers in the apolipoprotein B gene (XbaI, EcoRI, MspI, Ins/Del, and 4311 A/G polymorphisms) were evaluated in patients with ischemic cerebrovascular disease (ICVD) and controls of equivalent BMI. The odds ratio for ICVD in the X+X+ genotype was 2.22, 95% CI 1.24-3.96 (P<0.05), while that for ICVD in the Ins/Ins genotype was 2.82, 95% CI 1.57-5.06 (P<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…APOB protein is a component of chylomicrons, low-density lipoproteins (LDL), very low-density lipoproteins (VLDL), intermediate density lipoproteins (IDL) and functions as the main protein for transporting cholesterol to peripheral cells [1][2][3][4][5][6] . The plasma concentration of APOB protein reflects the total number of potentially atherogenic particles 2,4 and, therefore, is predictive of high risk of coronary heart disease that may not be otherwise detected from routine lipid profile 2,[7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…APOB protein is a component of chylomicrons, low-density lipoproteins (LDL), very low-density lipoproteins (VLDL), intermediate density lipoproteins (IDL) and functions as the main protein for transporting cholesterol to peripheral cells [1][2][3][4][5][6] . The plasma concentration of APOB protein reflects the total number of potentially atherogenic particles 2,4 and, therefore, is predictive of high risk of coronary heart disease that may not be otherwise detected from routine lipid profile 2,[7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The plasma concentration of APOB protein reflects the total number of potentially atherogenic particles 2,4 and, therefore, is predictive of high risk of coronary heart disease that may not be otherwise detected from routine lipid profile 2,[7][8][9][10] . High APOB protein level in blood is correlated with cerebrovascular and coronary artery diseases as well as increased risk of diabetes 1,3,11,12 . Variable number of tandem repeats (VNTRs), also known as minisatellites, comprise a significant portion (~3%) of the human genome 13 .…”
Section: Introductionmentioning
confidence: 99%
“…ApoB polymorphisms (T71I (c>t; rs17246849), A591V (c>t; rs17240681), BfaI (P2712L; c>t; rs17240903), MspI (R3611Q; g>a; rs17247291), EcoRI (E4154K; g>a; rs1042031), and Eco57I (N4311S; a>g; rs17240958), p.Arg3500Gln, c.4311A>G) were examined in patients with IS. Only two studies found that apoB polymorphisms [105,106] were associated with IS risk. Zhang et al [107] found that C7673T polymorphism in apoB gene is associated with risk of ischemic cerebral infarction with family history in 47 Han Chinese patients.…”
Section: Candidate-gene Association Studies Of Ischemic Strokementioning
confidence: 99%